2013
DOI: 10.1007/s11745-013-3835-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary CLA‐induced Lipolysis Is Delayed in Soy Oil‐Fed Mice Compared to Coconut Oil‐Fed Mice

Abstract: Conjugated linoleic acid (CLA) has been shown to cause a reduction in obesity in several species. CLA-induced body fat loss is enhanced when mice are fed coconut oil (CO) and involves increased lipolysis. The objective of this paper was to determine if the CLA-induced lipolysis in mice fed with different oil sources was time-dependent. Mice were fed 7 % soybean oil (SO) or CO diets for 6 week and then supplemented with 0 or 0.5 % CLA for 3, 7, 10 or 14 days. Body fat and ex-vivo lipolysis was determined. Body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There was described that the dietary supplementation with CO in humans promotes a reduction in abdominal obesity, but with a tendency to increase insulin resistance [28,29]. CO also potentiated the conjugated linoleic acid in lipolysis induction and lipogenesis diminution in mice [30], resulting in weight loss [31]. On the other hand, an observational study in 1981 reported that Pacific Island inhabitants in consuming higher amounts of CO were heavier and presented subscapular skin folds major [32].…”
Section: Co and Nashmentioning
confidence: 99%
“…There was described that the dietary supplementation with CO in humans promotes a reduction in abdominal obesity, but with a tendency to increase insulin resistance [28,29]. CO also potentiated the conjugated linoleic acid in lipolysis induction and lipogenesis diminution in mice [30], resulting in weight loss [31]. On the other hand, an observational study in 1981 reported that Pacific Island inhabitants in consuming higher amounts of CO were heavier and presented subscapular skin folds major [32].…”
Section: Co and Nashmentioning
confidence: 99%